From Archives to Action: Zines, Participatory Culture, and Community Engagement in Asian America - Honma, Todd (Radical Teacher, 2016)
As a pedagogical tool, zines exist at the intersection of radical history, analog creativity, participatory culture, and community engagement. This article highlights the importance of contextualizing zines within a history of social activism to shift the focus of zines from individualism and self motivation to their role in community empowerment and social justice. This is particularly relevant when teaching about the topic of Asian American zines and community engagement. The first half of this article discusses the use of Densho’s online archive of the complete print run of the Asian American movement periodical Gidra as a way to teach students about histories of Asian American independent publishing, racial formation, and community activism. The second part of this article moves from archives to practice, concerning how students can use the skills and knowledge that they learn from these archival materials and apply them to current events and community engagement projects surrounding gentrification and tenants’ rights in Los Angeles Chinatown.